- Trending Categories
- Data Structure
- Networking
- RDBMS
- Operating System
- Java
- MS Excel
- iOS
- HTML
- CSS
- Android
- Python
- C Programming
- C++
- C#
- MongoDB
- MySQL
- Javascript
- PHP
- Physics
- Chemistry
- Biology
- Mathematics
- English
- Economics
- Psychology
- Social Studies
- Fashion Studies
- Legal Studies

- Selected Reading
- UPSC IAS Exams Notes
- Developer's Best Practices
- Questions and Answers
- Effective Resume Writing
- HR Interview Questions
- Computer Glossary
- Who is Who

# Answer the following and justify:

If on division of a polynomial $ p(x) $ by a polynomial $ g(x) $, the quotient is zero, what is the relation between the degrees of $ p(x) $ and $ g(x) $ ?

Given:

On division of a polynomial \( p(x) \) by a polynomial \( g(x) \), the quotient is zero.

To do:

We have to find the relation between the degrees of \( p(x) \) and \( g(x) \).

Solution:

If on division of a polynomial p(x) by a polynomial g(x), the quotient is zero, then the relation between the degrees of p(x) and g(x) is the degree of p(x) is less than the degree of g(x).

For example,

$p(x)=10x$ and $g(x)=5x^2$

- Related Articles
- Answer the following and justify:If on division of a non-zero polynomial \( p(x) \) by a polynomial \( g(x) \), the remainder is zero, what is the relation between the degrees of \( p(x) \) and \( g(x) \) ?
- Divide the polynomial $p(x)$ by the polynomial $g(x)$ and find the quotient and remainder, in each of the following:$p(x) = x^4 - 5x + 6, g(x) = 2 -x^2$
- Divide the polynomial $p(x)$ by the polynomial $g(x)$ and find the quotient and remainder, in each of the following:$p(x) =x^4 - 3x^2 + 4x + 5, g(x) = x^2 + 1 -x$
- divide the polynomial $p( x)$ by the polynomial $g( x)$ and find the quotient and remainder in each of the following: $( p(x)=x^{3}-3 x^{2}+5 x-3$, $g(x)=x^{2}-2$.
- Divide the polynomial $p(x)$ by the polynomial $g(x)$ and find the quotient and remainder, in each of the following:(i) $p(x) = x^3 - 3x^2 + 5x -3, g(x) = x^2-2$(ii) $p(x) =x^4 - 3x^2 + 4x + 5, g(x) = x^2 + 1 -x$(iii) $p(x) = x^4 - 5x + 6, g(x) = 2 -x^2$
- On dividing $x^3 - 3x^2 + x + 2$ by a polynomial $g(x)$, the quotient and remainder were $x - 2$ and $-2x + 4$, respectively. Find $g(x)$.
- Find the zero of the polynomial:$P(x)=x- 5x+6$
- Answer the following and justify:Can \( x^{2}-1 \) be the quotient on division of \( x^{6}+2 x^{3}+x-1 \) by a polynomial in \( x \) of degree 5 ?
- Answer the following and justify:What will the quotient and remainder be on division of \( a x^{2}+b x+c \) by \( p x^{3}+q x^{2}+r x+s, p ≠ 0 ? \)
- Find the zeros of the polynomial \( x^{2}+x-p(p+1) \).
- Check whether the first polynomial is a factor of the second polynomial by applying the division algorithm:$g(x)\ =\ x^3\ –\ 3x\ +\ 1;\ f(x)\ =\ x^5\ –\ 4x^3\ +\ x^2\ +\ 3x\ +\ 1$
- Find the zero of the polynomial in each of the following cases:(i) \( p(x)=x+5 \)(ii) \( p(x)=x-5 \)(iii) \( p(x)=2 x+5 \)(iv) \( p(x)=3 x-2 \)(v) \( p(x)=3 x \)(vi) \( p(x)=a x, a ≠ 0 \)(vii) \( p(x)=c x+d, c ≠ 0, c, d \) are real numbers.
- Use the Factor Theorem to determine whether \( g(x) \) is a factor of \( p(x) \) in each of the following cases:(i) \( p(x)=2 x^{3}+x^{2}-2 x-1, g(x)=x+1 \)(ii) \( p(x)=x^{3}+3 x^{2}+3 x+1, g(x)=x+2 \)(iii) \( p(x)=x^{3}-4 x^{2}+x+6, g(x)=x-3 \)
- Check whether the first polynomial is a factor of the second polynomial by applying the division algorithm:$g(x)\ =\ 2x^2\ –\ x\ +\ 3;\ f(x)\ =\ 6x^5\ −\ x^4\ +\ 4x^3\ –\ 5x^2\ –\ x\ –\ 15$
- In each of the following, use factor theorem to find whether polynomial $g(x)$ is a factor of polynomial $f(x)$ or, not.$f(x) = x^3 - 6x^2 + 11x - 6; g(x) = x - 3$

Advertisements